WATER ALUMINIUM AND ALZHEIMER DISEASE - G.T.SHINDE,; S.S.UGLE,; M.D.BIKKAD,; S.B.INGLE, (International Journal of Pharma and Bio Sciences, 2015)
There is an interesting correlation between the incidence of Alzheimer disease and similar memory disorders and the amount of aluminum in drinking water. A study published in lancet, shown the geographical relationship between the aluminum content of drinking water and prevalence of Alzheimer disease over a ten year period.This study was undertaken to determine aluminum content of the well water and treated tap water supplied by the Municipal corporation and correlates with the increasing incidence of Alzheimer disease in Marathwada region .There is statistical significance of aluminum level between well and tap municipal water. As per various texts and researchers find out that 0.2 mg/lit is permissible value .So we can find out ratio that is 2.0245/ 0.2=10.1225.So we conclude that our study shows that tap water has ten times more aluminum content as compared to permissible value. There is also significant increasing Alzheimer cases (3.7) times during year 2001 to 2007 as compared with year 1994 to 2001.